Effects of a Six-Month Local Vibration Training on Bone Density, Muscle Strength, Muscle Mass, and Physical Performance in Postmenopausal Women. Issue 9 (September 2015) - Tankisheva, Ekaterina; Bogaerts, An; Boonen, Steven; Delecluse, Christophe; Jansen, Paul; Verschueren, Sabine M.P.
Abstract : Abstract: Tankisheva, E, Bogaerts, A, Boonen, S, Delecluse, C, Jansen, P, and Verschueren, SMP. Effects of a six-month local vibration training on bone density, muscle strength, muscle mass, and physical performance in postmenopausal women. J Strength Cond Res 29(9): 2613–2622, 2015—The aim of the study was to investigate the effect of 6 months' local vibration training on bone mineral density (BMD), muscle strength, muscle mass, and physical performance in postmenopausal women (66–88 years). The study was organized as a randomized controlled trial for postmenopausal women who lived in daily care service flats and rest homes. Thirty-five postmenopausal women were randomly assigned to either a vibration ( n = 17) or a control group ( n = 18). The vibration group received 6-month local vibration treatment with frequency between 30 and 45 Hz and acceleration between 1.71 and 3.58 g . The vibration was applied on the midthigh and around the hip in supine-lying position once per day, 5 d·wk −1 . The participants of the control group continued their usual activities and were not involved in any additional training program. The primary outcome variables were the isometric and dynamic quadriceps muscle strength and the BMD of the hip. We assessed the muscle mass of the quadriceps and physical performance. Additionally, the feasibility, side effects, and compliance were evaluated after 6 months of local vibration training. Overall, the results showed a net benefit of 13.84% in isometric muscle strength at 60° knee angle in favor of the vibration group compared with controls ( p < 0.01). No changes in BMD, muscle mass, or physical performance were found in both groups ( p > 0.05). Six months of local vibration training improved some aspects of muscle strength but had no effect on BMD, muscle mass, and physical performance in postmenopausal women. The specific vibration protocol used in this study can be considered as safe and suitable for a local vibration training program.